Susceptibility of Pets to SARS-CoV-2 Infection: Lessons from a Seroepidemiologic Survey of Cats and Dogs in Portugal - Barroso, Ricardo (2022)
Betacoronavirus (β-CoV) are positive single-stranded RNA viruses known to infect mammals. In 2019, a novel zoonotic β-CoV emerged, the severe acute respiratory syndrome (SARS)-CoV-2. Although the most frequent SARS-CoV-2 transmission route is within humans, spillover from humans to domestic and wild animals has been reported, including cats (Felis catus), dogs (Canis lupus familiaris), and minks (Neovision vision). In order to understand the potential role of domestic animals in SARS-CoV-2 global transmission, as well their susceptibility to infection, a seroepidemiologic survey of cats and dogs in Portugal was conducted. Antibodies against SARS-CoV-2 were detected in 15/69 (21.74%) cats and 7/148 (4.73%) dogs. Of the SARS-CoV-2 seropositive animals, 11/22 (50.00%) were possibly infected by human-to-animal transmission, and 5/15 (33.33%) cats were probably infected by cat-to-cat transmission. Moreover, one dog tested positive for SARS-CoV-2 RNA. Data suggest that cats and dogs are susceptible to SARS-CoV-2 infection in natural conditions. Hence, a one-health approach is crucial in the SARS-CoV-2 pandemic to understand the risk factors beyond infection in a human-animal environment interface.